Woman in Beauvoir’s Concept: A Feminist Reading - Bhatta, Damaru Chandra (DMC Research Journal, 2023)
The purpose of this paper is to present the French existentialist philosopher Simon de Beauvoir’s feminist viewpoint against traditional patriarchy, which is a social organization marked by the supremacy of the father in the clan or family, the legal dependence of wives and children, and the reckoning of descent and inheritance in the male line. It also tries to present her traditional analysis how woman has been unreasonably victimized by man in the society. Beauvoir shows with great erudition that man’s dominance has been secured through the ages by an ideological power; legislators, priests, scientists, and philosophers have all promoted the idea of woman’s subordination. Hence, Beauvoir concludes that feminist must break this type of patriarchal power to change man at the level of theory, but without entering the theoretical domain on man’s terms; however man and woman should live together for a happy life by enjoying equal right and power.